SENI PERTUNJUKAN CAN-MACANAN KADDHUK: PERGESERAN MAKNA KEARIFAN LOKAL MASYARAKAT JEMBER PADA ERA BERKELANJUTAN - Wahyuni, Lilik; Arifin, Nur Hikmah; Setiawati, Eti; Wijayanti, Jamila (Hiski Malang, 2023)
This research aims to describe the Performing Arts in Jember Regency. Can-Macanan Kaddhuk Performance Art is a performance art that is often performed in the Jember district. This art has experienced a shift in meaning over time. The purpose of this research is to describe the form of Can-Macanan Kaddhuk performance art, describe the existence of Can-Macanan Kaddhuk performance art in the millennial generation, and describe the shift in meaning or value of Can-Macanan Kaddhuk performance art. The method used in this research is descriptive qualitative with an ethnographic approach. The data collection techniques used are observation and interview techniques in the form of primary and secondary data. Primary data in this study, namely, the Can-Macanan Kaddhuk performance art and secondary data used, namely literature review in the form of relevant papers in this study. The results of this study indicate that the art of Can-Macanan Kaddhuk has experienced a shift in meaning caused by several factors, namely factors from within and factors from outside.